A Tale of Two Viruses: Immunological Insights Into HCV/HIV Coinfection - Gobran, Samaa T.; Ancuta, Petronela; Shoukry, Naglaa H. (Frontiers in Immunology, 2021)
Nearly 2.3 million individuals worldwide are coinfected with human immunodeficiency virus and hepatitis C virus (HCV). Odds of HCV infection are six times higher in people living with HIV (PLWH) compared to their HIV-negative counterparts, with the highest prevalence among people who inject drugs (PWID) and men who have sex with men (MSM). HIV coinfection has a detrimental impact on the natural history of HCV, including higher rates of HCV persistence following acute infection, higher viral loads, and accelerated progression of liver fibrosis and development of end-stage liver disease compared to HCV mono-infection. Similarly, it has been reported that HCV coinfection impacts HIV disease progression in PLWH receiving anti-retroviral therapies (ART) where HCV coinfection negatively affects the homeostasis of CD4+ T cell counts and facilitates HIV replication and viral reservoir persistence. While ART does not cure HIV, direct acting antivirals (DAA) can now achieve HCV cure in nearly 95% of coinfected individuals. However, little is known about how HCV cure and the subsequent resolution of liver inflammation influence systemic immune activation, immune reconstitution and the latent HIV reservoir. In this review, we will summarize the current knowledge regarding the pathogenesis of HIV/HCV coinfection, the effects of HCV coinfection on HIV disease progression in the context of ART, the impact of HIV on HCV-associated liver morbidity, and the consequences of DAA-mediated HCV cure on the immune reconstitution and HIV reservoir persistence in co-infected patients.